2020
DOI: 10.1111/1467-8500.12423
|View full text |Cite
|
Sign up to set email alerts
|

More ethical, more innovative? The effects of ethical culture and ethical leadership on realized innovation

Abstract: Are ethical public organisations more likely to realize innovation? The public administration literature is ambiguous about this relationship, with evidence being largely anecdotal and focused mainly on the ethical implications of business‐like behaviour and positive deviance, rather than how ethical behaviour and culture may contribute to innovation. In this paper we examine the effects of ethical culture and ethical leadership on reported realized innovation, using 2017 survey data from the Australia Public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 83 publications
(112 reference statements)
0
13
0
Order By: Relevance
“…A number of recent studies in the public sector setting have demonstrated that gender, age, working location, resources, work experience, education, and communication affect innovation and innovative behaviors (e.g. Bankins et al., 2017; Fernandez and Pitts, 2011; Nasi et al., 2011; Suseno et al., 2020; Torugsa and Arundel, 2016; Van der Wal and Demircioglu, 2020). According to descriptive statistics (see Table 1), 56% of the respondents were male and 44% were female.…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent studies in the public sector setting have demonstrated that gender, age, working location, resources, work experience, education, and communication affect innovation and innovative behaviors (e.g. Bankins et al., 2017; Fernandez and Pitts, 2011; Nasi et al., 2011; Suseno et al., 2020; Torugsa and Arundel, 2016; Van der Wal and Demircioglu, 2020). According to descriptive statistics (see Table 1), 56% of the respondents were male and 44% were female.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the components of work ethic are deemed to include the requirement to save time, reduce leisure time, as well as the precept not to consume rewards, as they change people's attitude towards other values. Also, worth mentioning are new research results on studies regarding the relationship of ethical culture and leadership with employees' innovation [25,26].…”
Section: Work Ethic As a System Of Attitudes And Beliefsmentioning
confidence: 99%
“…Thus, if both work ethics and intrinsic motivation are associated with job satisfaction and innovation [21,25,44], it can be assumed that the work ethic and motivation also show significant relationships. The important question is which components of ethics are most strongly associated with intrinsic motivation and which are weaker.…”
Section: Plos Onementioning
confidence: 99%
“…With regard to the implementation of sustainable or ethical orientation in companies, these focus in their implementation on the areas of processes, products and management. The focus is on clearly defined and standardised processes with a focus on sustainable products and a commitment to sustainability on the part of the management [19].…”
Section: Results Of the Online Surveymentioning
confidence: 99%
“…as entrepreneur, politician, customer or owner) and shows ethically "correct" (sustainable) behaviour here. From the literature, the following aspects can be named as the first relevant success factors for the formulation, operationalisation and implementation of ethical standards: existence of a sustainable corporate mission statement, existence of entrepreneurial resources, existence of a guiding regulatory framework, documentation of sustainable behaviour in the company as well as behaviour analogous to and measurement of entrepreneurial behaviour on indices and with the help of reporting standards [19,20].…”
Section: The State Of the Problem In The Literaturementioning
confidence: 99%